Lab-on-Chip for Exosomes and Microvesicles Detection and Characterization - Chiriacò, Maria Serena; Bianco, Monica; Nigro, Annamaria; Primiceri, Elisabetta; Ferrara, Francesco; Romano, Alessandro; Quattrini, Angelo; Furlan, Roberto; Arima, Valentina; Maruccio, Giuseppe (Sensors (Basel, Switzerland), 2018)
Interest in extracellular vesicles and in particular microvesicles and exosomes, which are constitutively produced by cells, is on the rise for their huge potential as biomarkers in a high number of disorders and pathologies as they are considered as carriers of information among cells, as well as being responsible for the spreading of diseases. Current methods of analysis of microvesicles and exosomes do not fulfill the requirements for their in-depth investigation and the complete exploitation of their diagnostic and prognostic value. Lab-on-chip methods have the potential and capabilities to bridge this gap and the technology is mature enough to provide all the necessary steps for a completely automated analysis of extracellular vesicles in body fluids. In this paper we provide an overview of the biological role of extracellular vesicles, standard biochemical methods of analysis and their limits, and a survey of lab-on-chip methods that are able to meet the needs of a deeper exploitation of these biological entities to drive their use in common clinical practice.